Isolation of the ZmERS4 Gene From Maize and Its Functional Analysis in Transgenic Plants - Hang, Tianlu; Ling, Xuezhi; He, Cheng; Xie, Shanshan; Jiang, Haiyang; Ding, Ting (Frontiers in Microbiology, 2021)
A gene encoding an ethylene receptor protein was isolated from maize (Zea mays L.), which was named ZmGRM4.The gene was 1,905 bp in length with an open reading frame that encoded a protein consisting of 634 amino acids. The homologous analysis showed that ZmGRM4 shared high similarity with the ethylene receptor protein, OsERS1, from rice (Oryza sativa L.). ZmGRM4 grouped into the ETR1 subfamily of ethylene receptors based on its conserved domain and phylogenetic status. Tissue-specific and induced expression analyses indicated that ZmGRM4 was differentially expressed in maize tissues, predominantly in the stems and leaves, and was induced by salicylic acid (SA). Overexpression of ZmGRM4 in Arabidopsis improved resistance against the pathogen, PstDC3000, by inducing the expression of SA signaling-related genes. Moreover, treatment with flg22 induced the expression of the defense-related gene, PR1, in maize protoplasts that transiently expressed ZmGRM4. Furthermore, the ultra-high-performance liquid chromatography (UPLC) analysis showed that the SA contents in ZmGRM4-overexpressing Arabidopsis lines were significantly higher than the control lines. Additionally, the improved resistance of ZmGRM4-overexpressing Arabidopsis against PstDC3000 was blocked after pretreatment with the SA biosynthetic inhibitor, ABT. Based on the collective findings, we hypothesize that ZmGRM4 plays an important role in disease resistance through SA-mediated signaling pathways.